Roller ski interval training in biathletes: Assessing whether athletes meet high-intensity targets on the track - Aschenbrenner, P.; Tomaszewska, A.; Ambroziak, A.; Grzywacz, T.; Woznica, W.; Krawczynski, M. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Accidents during skiing competitions occur randomly, are not subject of any real-time measurements and cannot be repeated in real conditions. One of the methods of investigating accidents is computer simulation, which take into account the inertial and kinetic parameters of the object [1,2]. There are papers with human numerical models described in the literature [1,2] and commercial models, but they do not take into account the specifics of a skier on skis. Based on the literature review, it can be concluded that there is no available specification of a skier model with ski equipment, and therefore the authors set a goal to develop a multi segment model of a skier with ski equipment.